Dramaturgia da harmonia: uma encenação musical por Arnold Schoenberg - Sant'Ana, Doriedison Coutinho de (Revista do Colóquio, 2021)
This article intends to show, from the perspective of the staging, the playfulness and imagination of the musician Arnold Schoenberg when speaking about the behavior of sound events in the process modulation within the Musical Harmony. "Drawing" sound movements and transforming them into musical art is an activity that requires the inventor / composer to pay close attention to the issues of the art of movement. It is necessary to create combinations that sound like art. Therefore, it is essential to know the language of music well and, on the other hand, to "see" in the sound movements something extra-musical, to perceive beyond the obvious, to imagine a certain "fable" happening between the sounds. To demonstrate this, we will make parallels between the melodic creation and the staging of an actor, casting a kind of fabulous look on the first pages of the chapter “Modulation”, from the book “Harmonia”.